The Golden Egg : Commissario Brunetti #22 - Leon, Donna (New York : Atlantic Monthly Press, 2013)
At the request of his wife, Commissario Brunetti looks into the death of deaf, mentally disabled man who worked at their dry-cleaners and uncovers a mystery when the man left no official records and his mother is reluctant to speak to him.
Originally published: London : William Heinemann, 2013.
Map on lining papers.
Keywords: Brunetti, Guido (Fictitious character) -- Fiction; Police -- Fiction -- Italy -- Venice -- Fiction; Brunetti, Guido (Fictitious character) -- Fiction; Police -- Italy -- Venice -- Fiction; Venice (Italy) -- Fiction; Venice (Italy) -- Fiction; Mystery fiction